Mutant Prevention Concentrations of Imipenem and Meropenem against Pseudomonas aeruginosa and Acinetobacter baumannii - E. Dahdouh; S. H. Shoucair; S. E. Salem; Z. Daoud (The Scientific World Journal)
The aim of this study was to determine the usefulness of the MPC of carbapenems against clinical isolates of Pseudomonas spp. and Acinetobacter spp. and to assess its possible relationship with mechanisms of resistance. Detection of the mechanisms of resistance was performed using Antibiotic Susceptibility Testing, Double Disk Synergy, disk antagonism, addition of NaCl to the medium, addition of PBA or EDTA to Carbapenem disks, addition of PBA to Cefoxitin disks, and CCCP test for 10 Pseudomonas spp. and Acinetobacter baumannii strains. The MIC and MPC were determined using the broth macrodilution and plate dilution methods, respectively. Four Acinetobacter baumannii strains produced MBL. Two of them produced Oxacillinase and one produced ESBL. Two Pseudomonas spp. isolates produced both KPC and MBL. The resistant Acinetobacter spp. and Pseudomonas spp. strains had higher MPC values than susceptible ones. However, the Mutant Selection Window was found to be dependent on the degree of resistance but not on a particular mechanism of resistance. The usefulness of the MPC was found to be dependent on its value. Based on our data, we recommend determining the MPC for each isolate before using it during treatment. Furthermore, the use of T>MSW instead of T>MIC is suggested.